Diferentes procedimentos na determinação de indicadores internos para estimativa de produção fecal e fluxo duodenal de matéria seca em bovinos - Da Silva Morais, Jucileia Aparecida; Berchielli, Telma Teresinha [UNESP]; De Oliveira, Simone Gisele; Queiroz, Maria Fernanda Soares; Toro-Velásquez, Paula Andrea [UNESP]; Rivera-Rivera, Astrid [UNESP] (Universidade Estadual de Maringa, 2010)
Times of in situ incubation (144 and 288h) for determination of internal markers IADF and INDF and the effects of differents procedures (wash or not the nylon bag every 72h incubation) was evaluated in samples of diet, duodenal digesta and cattle feces. The duodenal flow dry matter and fecal production utilizing the internal markers to compare with the external marker chromium oxide there was estimated. The animals were fed with sorgum silage, concentrate or urea. In this experiment, a latin square design was used, in a factorial scheme (two times of incubation × two processing nylon bag). No was observed effect of the incubation time or processing in the internal markers INDF and IADF concentration and the in situ incubation after 144h is adequate to reproduce the indigestible markers fraction in samples. For fecal production estimation, the external marker chromium oxide presented similar result (1.26 kg day-1) as the total fecal collection (1.49 kg day-1). Both the internal markers overestimate the duodenal flow dry matter when compared with the external marker chromium oxide.
Different procedures for internal markers determination in fecal production and duodenal flow of dry matter estimate in cattle
Keywords: IADF; Incubation procedure; INDF; Animalia; Bos